Changes in Astigmatism After Phacoemulsification with a Superior Incision (Majalah Kedokteran Bandung, 2025)
Surgically induced astigmatism (SIA) is a common phacoemulsification procedure for senile cataracts. The size, location, and incision type significantly influence the SIA degree. This study aimed to evaluate the effect of a superior incision on astigmatism levels in patients both before and after phacoemulsification for senile cataracts. This retrospective analytical observational study utilized a cohort at Sultan Agung Islamic Hospital, Semarang, Indonesia, between November 2023 and May 2024. The accessible population consisted of patients treated during the study period. A total of 65 eyes from patients who underwent phacoemulsification with a superior incision were included in the study. Twenty-five patients (38.5%) exhibited against-the-rule (ATR) astigmatism before the surgical procedure, which decreased to 16 patients (24.6%) following surgery. In contrast, after phacoemulsification with a superior incision, the number of patients with with-the-rule (WTR) astigmatism increased from 61.5% to 75.4%. The astigmatism value before phacoemulsification with a superior incision was 1.274±1.02, while the value was 0.945±1,02 afterwards. The Wilcoxon Test revealed a significant difference (p
Keywords: phacoemulsification; senile cataracts; superior corneal incision; surgically induced astigmatism